Understanding the role of tissue-specific decellularized spinal cord matrix hydrogel for neural stem/progenitor cell microenvironment reconstruction and spinal cord injury. (January 2021) - Xu, Yiwei; Zhou, Jing; Liu, Cuicui; Zhang, Sheng; Gao, Fenglin; Guo, Wenjing; Sun, Xiumin; Zhang, Chi; Li, Heying; Rao, Zilong; Qiu, Shuai; Zhu, Qingtang; et al.
Abstract: The repair of spinal cord injury (SCI) highly relies on microenvironment remodeling and facilitating the recruitment and neuronal differentiation of endogenous stem/progenitor cells. Decellularized tissue matrices (DTMs) have shown their unique and beneficial characteristics in promoting neural tissue regeneration, especially those derived from the nervous system. Herein, we present a comparative analysis of a DTM hydrogel derived from spinal cord (DSCM-gel) and a decellularized matrix hydrogel derived from peripheral nerves (DNM-gel). The tissue-specificity of DSCM-gel was evaluated both in vitro, using neural stem/progenitor cell (NSPC) culture, and in vivo, using various materials and biological analyses, including transcriptome and proteomics. It was found that DSCM-gel retained an extracellular matrix-like nanofibrous structure but exhibited higher porosity than DNM-gel, which potentiated NSPCs viability, proliferation, and migration in the early stage of 3D culturing, followed by facilitation of the NSPCs differentiation into neurons. Transcriptome analysis indicated that DSCM-gel regulates NSPCs behavior by modulating integrin α2, α9, and β1 expression profiles along with AKT/ERK related signaling pathways. Proteomics analyses suggest that DSCM specific extracellular matrix proteins, such as the tenascin family (TNC) and some soluble growth factor (FGF2) may contribute to these regulations. Furthermore, in vivo assessments confirmed that DSCM-gel provides a suitable microenvironment for endogenous stem/progenitor cell recruitment and axonal regeneration for bridging the lesion site after a completely transected SCI. Thus, this systematic study provides key insights useful for the development of the tissue-specific DTM biomaterials for translational microenvironment replacement therapies and tissue repair. Graphical abstract: Image 1